Development of Web Bases Inquiry Learning with the Flipped Classroom Model in Science Learning for 7th Grade of Junior High School - Deni Ranoptri; Mustaji Mustaji; Bachtiar Syaiful Bachri (IKIP Mataram, 2022)
This research aims to produce inquiry web-based learning multimedia valid and effective way to improve student learning outcomes on ecosystem materials in junior high schools. This research is a development research that will be carried out in two stages (the development stage of learning multimedia and the stage of testing the results of multimedia). The product developed was validated by (how many validators) competent experts and then tested empirically using Randomized Control-Group Pretest-Posttest Design on (how many students) students. The research data were analyzed descriptively and statistically. The results showed that (1) inquiry web-based learning multimedia was declared valid with very high criteria (individual test n=3, achievement= 92%; small group test n= 9, achievement= 86%; and large group test n= 32, achievement = 79%) and (2) the increase in learning outcomes of the experimental group was significantly different compared to the control group. Based on the research findings, it can be concluded that the inquiry web -based learning multimedia developed is valid and effective f in improving the learning outcomes of class VII junior high school students on the material of the ecosystem of the Biology Science subject.